A Primary Extraskeletal Osteosarcoma of the Spleen: Rare Case Report - Pan, Xian; Wang, Han-Lu; Lin, Shi-Ming; Lin, Jia-Li; Ruan, Dan-Dan; Zhang, Jian-Hui; Chen, Ting; Luo, Jie-Wei; Fang, Zhu-Ting (Frontiers in Oncology, 2022)
Background: Extraskeletal osteosarcoma(ESOS) is a very rare malignant soft tissue sarcoma, and it is difficult to diagnose. Surgery is a common treatment, and chemotherapy and radiotherapy are also involved in the treatment of this disease. Patients at risk of bleeding can use embolization combined with resection. As far as we know, primary splenic extraskeletal osteosarcoma has not been reported in the literature at present. Materials and Methods: A 50-year-old female who complained of pain in the left upper abdomen for one day was initially diagnosed as "splenic hemangioma with high possibility of rupture and bleeding" and urgently underwent digital subtraction angiography(DSA)combined with splenic arteriography and embolization. Abdominal pain worsened 2 days after operation, hemoglobin showed 106.0g/L, and emergency laparotomy combined with splenectomy was performed. The clinical, imaging features, pathological diagnosis and embolization treatment of this case were analyzed retrospectively. Results: Computed tomography (CT) of the upper abdomen showed splenomegaly, irregular low-density shadow in the spleen, and flake-like calcification in the lateral margin of the left kidney. Nuclear magnetic resonance imaging (MRI) of the upper abdomen showed splenomegaly, mass occupying (about 8.4cm×5.7cm×6.3cm)below the spleen,with clear boundary,uneven signal slightly low on T1WI and slightly high on T2WI;samll cystic degeneration or cystic spaces inside showed a longer T2WI signal,the lesion showed gradual enhancement,the enhancement range incresed on delayed scan;hematoma below the spleen capsule and calcification below the lesion(nodular T1WI/T2WI hypointense,about 3.3cm×3.6cm). Postoperative biopsy pathology showed splenic soft tissue tumor: At low magnification, the multinucleated giant cells were scattered; At medium magnification, there were osteoclast-like multinucleated giant cells; At high magnification, tumor osteogenesis can be seen, which is lace-like or grid-like.The immunohistochemistry showed that CD31, CD34, F8, s-100, desmin, SMA, and CD99 expressions were negative, while β-catenin, BCL-2, SATB-2, and P16 expressions were positive. CD68 and MDM-2 showed small amounts of expression, while Ki-67 expression was 50% positive. No abnormal concentration of radioactivity was found in the patient by single-photon emission computed tomography (SPECT) with 99mTc-MDP after operation . Conclusion: In summary, the case was diagnosed with primary extraskeletal osteosarcoma. It is necessary for Multi disciplinary team (MDT) to make malignant ESOS diagnosis.